2017
DOI: 10.1007/s40314-016-0414-9
|View full text |Cite
|
Sign up to set email alerts
|

On convergent finite difference schemes for variational–PDE-based image processing

Abstract: We study an adaptive anisotropic Huber functional based image restoration scheme. By using a combination of L2-L1 regularization functions, an adaptive Huber functional based energy minimization model provides denoising with edge preservation in noisy digital images. We study a convergent finite difference scheme based on continuous piecewise linear functions and use a variable splitting scheme, namely the Split Bregman [25], to obtain the discrete minimizer. Experimental results are given in image denoising a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The matrix A l = (a ijl ) ij corresponds to derivatives along the l-th coordinate axis. Note that this involves solving a linear system where the system matrix is tridiagonal and diagonally dominant, see [74,59] for more details. To avoid the directional (x-y axis) smoothing bias we adapted a multi-direction based modification [58] , and to be fair the same approach was used to compare all the PDEs here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The matrix A l = (a ijl ) ij corresponds to derivatives along the l-th coordinate axis. Note that this involves solving a linear system where the system matrix is tridiagonal and diagonally dominant, see [74,59] for more details. To avoid the directional (x-y axis) smoothing bias we adapted a multi-direction based modification [58] , and to be fair the same approach was used to compare all the PDEs here.…”
Section: Resultsmentioning
confidence: 99%
“…We do not use a notation for partial time derivative since we treat (59) as an ODE in a Banach space.…”
Section: Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…(3), called structure tensor adaptive total variation (STATV), obtains better restoration results as we will in the experimental results (Section 3). There exist many convergent numerical implementations [12] for the TV regularization that can be adapted for the ATV model considered here. However, we utilize the well-known split Bregman algorithm [8] to solve the adaptive TV regularization in Eq.…”
Section: Adaptive Total Variationmentioning
confidence: 99%
“…Fixing a parameter with these standard parameter estimation methods can still lead to poor results, since the regularization needs to be reduced in the iterative implementation. Recently data adaptive methods (Fu, Zhang, 2010, Prasath, Singh, 2010, Wang et al, 2011, Prasath, 2011, Prasath, Moreno, 2018 are found to provide better solutions, though with higher computational overhead.…”
Section: Introductionmentioning
confidence: 99%